The effect of priming on fraud: Evidence from a natural field experiment - Parampreet Christopher Bindra; Graeme Pearce (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We present a natural field experiment designed to examine the extent to which priming can influence the behaviour of sellers in a real world market for credence goods. We employed 40 testers to take 600 taxi journeys in and around Vienna, Austria. Using a between-subject design we vary the script spoken by testers, with each script designed to prime either honest behaviour, dishonest behaviour, or the existence of a market competitor. In contrast to our hypotheses, we find that priming honesty increases taxi fares by 5% in comparison to a baseline, increasing the frequency of overcharging by 15% and the amount overcharged by around 44%. The dishonesty prime has no impact. The market competitor prime increases both overcharging and overtreatment by amounts that are individually indistinguishable from zero, but jointly raise fares by 5%. All of the treatments are found to have no significant effect on journey length (overtreatment).
Keywords: C93; 330; Fraud; Credence Goods; Priming; Field Experiment